2009
DOI: 10.1182/blood-2008-07-168351
|View full text |Cite
|
Sign up to set email alerts
|

Increased T-bet+ cytotoxic effectors and type I interferon–mediated processes in chronic graft-versus-host disease of the oral mucosa

Abstract: Although chronic graft-versus-host disease (cGVHD) is a major long-term complication of allogeneic hematopoietic stem cell transplantation, little is known of its pathogenesis. We have systematically examined oral mucosa among cGVHD patients and determined that the clinical severity of oral cGVHD was correlated with apoptotic epithelial cells, often found adjacent to infiltrating effector-memory T cells expressing markers of cytotoxicity and type I cytokine polarization. Accumulation of T-bet ؉ T-cell effector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 51 publications
7
92
0
1
Order By: Relevance
“…47 Our studies confirm these data, [47][48][49] ie, an upregulation of chemokines of the CXCR3 family, and further demonstrate an overexpression of CCL5 and CCR5. We would therefore propose that both the CXCR3 and CCR5 pathways are critically involved in the attraction of pathogenic lymphocytes to clGVHD skin.…”
Section: Cells In Cutaneous Gvhd 297supporting
confidence: 79%
“…47 Our studies confirm these data, [47][48][49] ie, an upregulation of chemokines of the CXCR3 family, and further demonstrate an overexpression of CCL5 and CCR5. We would therefore propose that both the CXCR3 and CCR5 pathways are critically involved in the attraction of pathogenic lymphocytes to clGVHD skin.…”
Section: Cells In Cutaneous Gvhd 297supporting
confidence: 79%
“…13 In both human and mouse autoimmune disease studies, the binding of CXCL9 to CXCR3 promotes lymphocyte migration to inflamed tissues. 17,18 CXCR3 has also been shown to be critical for the recruitment of alloreactive T cells in aGVHD, 19,20 whereas CXCL9 has been shown to be elevated in tissue samples from patients with oral, 21 ocular, 22 and cutaneous 23 cGVHD. We found that the plasma of patients with newly diagnosed cGVHD, but not established cGVHD, contains higher concentrations of CXCL9 than patients without cGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…43 The ability of this cytokine to induce fibrotic responses within fibroblasts and scleroderma in the absence of SOCS3 is thus not surprising. In contrast IFN␥ generation after BMT is almost entirely derived from the donor T cell and, although the mechanism by which this cytokine may promote fibrosis is unclear, the association has been made with clinical chronic GVHD 44 and systemic sclerosis. 45 Although animal studies have shown that autoimmune "chronic" GVHD may occur in a Th1-dependent fashion, 46 these studies do not induce the fibrosis that is characteristic of clinical chronic GVHD.…”
Section: Socs3 Regulates Gvhd 293mentioning
confidence: 99%